The Tendency Towards Entrepreneurship Among Students of Maktab Rendah Sains Mara (MRSM) - Nordalila Binti Mohammad Rasid; Nor Aishah Buang (Universitas Muhammadiyah Surakarta, 2019)
In this globalization’s era, entrepreneurship is one of the catalyst that related to the economy, enhancing innovation, creativity and competitive for a country. Based on that scenario, the entrepreneurial field today is developing rapidly in our country Malaysia through our educational system. So, this research was carried out to find out the tendencies among the students of Maktab Rendah Sains MARA (MRSM) in the field of entrepreneurship. This research was using descriptive method through quantitative approach. The questionnaire used as the research instrument by using the Likert Scale. All the data s obtained then analyzed using the Statistical Packages for Social Sciences (SPSS) version 22. All the respondent were 108 students of MRSM who had been chosen by simple random. The result showed that attitude was the main dimension that influenced student to be involve in entrepreneurship. Beside that, the result also showed that there was no slightly significant differences in the item of gender factor in entrepreneurship tendency among those students.